Why Canada Is in Court to Protect Healthcare for All: Global Implications for Universal Health Coverage - Frank, John; Pagliari, Claudia; Donaldson, Cam; Pickett, Kate E.; Palmer, Karen S. (Frontiers in Health Services, 2021)
Countries worldwide are currently endeavoring to safeguard the long-term health of their populations through implementing Universal Health Coverage (UHC), in line with the United Nation's 2015-30 Sustainable Development Goals (SDGs). Canada has some of the world's strongest legislation supporting equitable access to care for medically necessary hospital and physician services based on need, not ability to pay. A constitutional challenge to this legislation is underway in British Columbia (BC), led by a corporate plaintiff, Cambie Surgeries Corporation (CSC). This constitutional challenge threatens to undermine the high bar for UHC protection that Canada has set for the world, with potential adverse implications for equitable international development. CSC claims that BC's healthcare law—the Medicare Protection Act (MPA)—infringes patients' rights under Canada's constitution, by essentially preventing physicians who are enrolled in BC's publicly-funded Medicare plan from providing expedited care to patients for a private fee. In September 2020, after a trial that ran for 3.5 years and included testimony by more than 100 witnesses from around the world, the court dismissed the plaintiffs' claim. Having lost their case in the Supreme Court of BC, the plaintiffs' appealed in June 2021. The appellate court's ruling and reasons for judgment are expected sometime in 2021. We consider the evidence before the court from the perspective of social epidemiology and health inequalities, demonstrating that structural features of a modern society that exacerbate inequalities, including inequitable access to healthcare, can be expected to lead to worse overall societal outcomes.